Impact of Social-media Engagement and Entertainment on the Buying Intention from Online Fashion Stores in Jordan - Alnsour, Iyad (Jordan Journal of Business Administration, 2024)
This study aimed to determine the effect of engagement and entertainment on buying intention of young Jordanians from fashion stores via Facebook and to determine statistical differences according to gender, income, level of education and place of residence. The research population consisted of all young users of Facebook in Jordan. The actual population size reached 1.501 million young people. The non-probability sampling technique through the snowball method was used. The sample size was 515 from the five most popular online stores in the fashion industry in Jordan: Fordeal, Jollychic, Noon Shopping, Vova and Dokanati. The independent variable (IV) was social-media usage, consisting of two sub-variables: engagement and entertainment. The buying intention was the dependent variable (DV). The study concluded that the level of response of IV and DV is moderate. The study also found a moderate impact of social-media usage on the buying intention from e-fashion stores via Facebook. The study also found no statistical differences in the level of DV according to gender, income, education and place of residence. Finally, the study recommended a national plan for SMM and establishing a national non-profit training center concerned with spreading the culture of SMM.